2013
DOI: 10.1093/brain/awt281
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a determinant of relapse incidence and progressive course of multiple sclerosis

Abstract: The aim of this work was to evaluate sex differences in the incidence of multiple sclerosis relapses; assess the relationship between sex and primary progressive disease course; and compare effects of age and disease duration on relapse incidence. Annualized relapse rates were calculated using the MSBase registry. Patients with incomplete data or <1 year of follow-up were excluded. Patients with primary progressive multiple sclerosis were only included in the sex ratio analysis. Relapse incidences over 40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
100
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 26 publications
16
100
0
2
Order By: Relevance
“…These effects causing increased disease risk may be present already during the fetal period and in the childhood, supported by the fivefold F/M ratio among RRMS cases younger than 20 years as was seen in this study. This result corroborates observations of a higher relapse rate among females and the effect of age and disease duration on disease activity [33]. …”
Section: Discussionsupporting
confidence: 91%
“…These effects causing increased disease risk may be present already during the fetal period and in the childhood, supported by the fivefold F/M ratio among RRMS cases younger than 20 years as was seen in this study. This result corroborates observations of a higher relapse rate among females and the effect of age and disease duration on disease activity [33]. …”
Section: Discussionsupporting
confidence: 91%
“…A number of previous studies, including large cohort studies and a meta-analysis of 33 observational studies of patients with CIS consistently showed that females are more likely to experience relapses throughout the course of the disease [42][43][44] ( table 1 ). Relapse incidence is known to decrease with time, represented either by patient age or by MS duration [20,42,[44][45][46][47][48] .…”
Section: Individual Risk Factors and Predictorsmentioning
confidence: 93%
“…Relapse incidence is known to decrease with time, represented either by patient age or by MS duration [20,42,[44][45][46][47][48] . In a direct comparison of the effects of these largely collinear determinants of relapse frequency, we showed that older age is relatively more closely associated with decline in relapse activity than MS duration [42] . Interestingly, our study suggested that an interaction between sex-and time-dependent changes in relapse frequency may exist, with the attenuation of relapse activity delayed in females com- pared to males.…”
Section: Individual Risk Factors and Predictorsmentioning
confidence: 99%
“…[9][10][11] We have recently demonstrated feasibility of propensitybased matching for evaluation of treatment effectiveness in the MSBase dataset, showing that two dosages of IFNβ-1a SC were equivalent in relapse rate and disability outcomes, thus mirroring the outcomes of the pivotal registration study. 12,13 Here we present a propensity score-matched analysis comparing the effectiveness of IFNβ and GA preparations in a series of pairwise head-to-head cohort studies conducted in MSBase.…”
Section: Introductionmentioning
confidence: 99%